Physical Activity during Pregnancy: Impact of Applying Different Physical Activity Guidelines - Katie M. Smith; Christina G. Campbell (Journal of Pregnancy)
Multiple guidelines and definitions of physical activity (PA) have been used to study the benefits of activity during pregnancy. The different guidelines lead to a wide range of prevalence estimates and this has led to conflicting reports about activity patterns during pregnancy. A longitudinal study was conducted to assess PA using a pattern-recognition monitor for a 7-day period at week 18 () and week 35 () of pregnancy. The amount of activity performed and the number of women meeting six different PA guidelines were evaluated. Adherence to PA guidelines ranged from 5 to 100% and 9 to 100% at weeks 18 and 35, respectively. All women achieved the 500 MET-minute guideline and nearly all women accumulated ≥150 minutes of weekly moderate-vigorous physical activity (MVPA) at both time points. Only 22% and 26% participated in ≥3 sessions of MVPA lasting ≥30 minutes at both time points and this further declined to 5% and 9% when the guideline was increased to ≥5 sessions of 30 minutes. The amount of PA during pregnancy varied drastically depending on which guideline was used. Further research is warranted to clearly identify the patterns of activity that are associated with healthy pregnancy outcomes.